Effects of Movement Direction through a Switch on Accelerations and Natural Frequencies of a Pneumatic Suspension of High-Speed Rolling Stock - Andrii Kuzyshyn; Vitalii Kovalchuk; Yuriy Royko (Communications)
The research object is a pneumatic spring of the second stage of spring suspension of the high-speed railway rolling stock in movement conditions by a switch. Full-scale dynamic tests of a pneumatic spring for the high-speed railroad rolling stock were carried out. It was found that the average values of vertical accelerations in the trailing and facing directions in the wind turbines moving by the switch are 1.307 m.s-2 and 1.279 m.s-2, respectively. The ratio of the average values of longitudinal accelerations in the trailing and facing directions within the wind turbines is 1.01, and at the wind turbine bases is 2.15. It is found that the average value of the first natural frequency of oscillations of the pneumatic spring is 3.53 Hz, while the logarithmic decrement of the oscillation attenuation is 0.321.